1995
DOI: 10.1002/ijc.2910640506
|View full text |Cite
|
Sign up to set email alerts
|

Expression of autocrine motility factor receptor in human esophageal squamous cell carcinoma

Abstract: Autocrine motility factor and its receptor (gp78) have been shown to play an important role in tumor cell migration, invasion and metastasis. We have detected gp78 expression in buffered-formalin-fixed, paraffin-embedded sections of esophageal squamous cell carcinomas using an anti-gp78 monoclonal antibody (MAb), 3F3A, and examined the relationship between gp78 expression and clinicopathological and prognostic factors. In 55 of 101 (54%) patients, gp78 was detected in the tumor cells. The frequency of gp78-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Nakamori S et al, [17] and Maruyama et al, [18] also reported absence of significant expression of AMFR in normal tissues Thus, generally AMFR is shown to be minimally expressed in normal tissues.…”
Section: Discussionmentioning
confidence: 93%
“…Nakamori S et al, [17] and Maruyama et al, [18] also reported absence of significant expression of AMFR in normal tissues Thus, generally AMFR is shown to be minimally expressed in normal tissues.…”
Section: Discussionmentioning
confidence: 93%
“…After rehydration and washing with phosphatebuffered saline (PBS, pH 7.2), sections were incubated with 10% normal goat serum (Dako, Glostrup, Denmark) in PBS for 20 min at room temperature to block non-specific binding of the second antibody. After blocking against endogenous avidin and biotin, sections were incubated with anti-gp78 monoclonal antibody, 3F3A (Nabi et al, 1990;Silletti et al, 1991;Nakamori et al, 1994;Otto et al, 1994;Maruyama et al, 1995) (Cox, 1972). The difference was considered to be significant when P was less than 0.05.…”
Section: Patientsmentioning
confidence: 99%
“…(Dako, Glostrup, Denmark) in PBS for 20 min at room temperature to block non-specific binding of the second antibody. After blocking against endogenous avidin and biotin, sections were incubated with anti-gp78 monoclonal antibody, 3F3A (Nabi et al, 1990;Silletti et al, 1991;Nakamori et al, 1994;Otto et al, 1994;Maruyama et al, 1995), at a dilution of 1:200 in PBS containing 1% bovine serum albumin (Sigma, St. Louis, MO, USA) overnight at 4°C. After three rinses in PBS, sections were incubated with biotinylated anti-rat immunoglobulin (Dako) for 1 h at room temperature, washed three times with PBS and reacted with streptoavidin-biotin system Correspondence: Y Hirono, Department of Surgery, Keiju General Hospital, Tomioka-cho 94, Nanao, Ishikawa, 926, Japan Received 5 January 1996; revised 7 June 1996; accepted 1 July 1996 (Dako), using 0.04% 3,3'-diaminobenzide tetrahydrochloride (Sigma) for 1 min as chromogen.…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations